Biodiversity of vesicular arbuscular mycorrhizal (VAM) fungi in horticultural production system in northern Rajasthan (Indian Journal of Arid Horticulture, 2025)
The diversity of vesicular arbuscular mycorrhizal (VAM) fungi in horticultural production systems of small farmer agro systems was analysis. Vesicular arbuscular mycorrhizal fungal symbioses are playing a key role for P uptake by horticultural crops grown there. The objective of this study was to determine AM fungal community's in cropping systems and to identify soil factors affecting their frequency and diversity. Totally 4 VAM fungal species were identified. It is concluded that it will be advisable for farmers to inoculate their horticultural crops with selected Mycorrhizal inoculants during the nursery stage, as it cannot be predicted from the soil conditions whether the native vesicular arbuscular mycorrhizal fungal community is sufficient to sustain a stable horticultural production in the region
Keywords: Glomeromycetes; Vesicular Arbuscular Mycorrhiza; soil; arid region and agro-ecosystems.